UNSTEADY FLOW OF THIXOTROPIC COLLAGEN SUBSTANCE IN PIPES - Rudolf Žitný; Aleš Landfeld; Jan Skočilas; Jaromír Štancl; Vlastimil Flegl; Milan Houška (Acta Polytechnica, 2015)
Unsteady flow of thixotropic liquid in pipes is solved by 1D and 2D numerical methods using the same constitutive equation — the only difference is in the radial diffusion of the structural parameter. Comparison shows that the neglected diffusion of structural parameter implicates a much stronger effect of thixotropy. The models are applied for analysis of the observed hysteresis of hydraulic characteristic of collagen.